New generic synomyms in the Chloropidae (Diptera, Acalyptratae), with additional taxonomic notes - Nartshuk, Emilia P.; Von Tschirnhaus, Michael (Zootaxa, 2012)
Myrmemorpha Dufour, 1833 and M. brachyptera Dufour, 1833 are considered as synonyms of Elachiptera Macquart, 1835 andE. brevipennis (Meigen, 1830), respectively (Oscinellinae). Pachychoeta Bezzi, 1895, Melanochaeta Bezzi, 1906 and Pachy-chaetina Hendel, 1907 are considered as synonyms of Oscinella Becker, 1909 as the type-species of these genera, Pachychoetaaterrima Bezzi, 1895 (= Oscinis capreolus Haliday, 1838), is transferred to the genus Oscinella Becker, 1909. LasiochaetaCorti, 1909 (type-species Elachiptera pubescens Thalhammer, 1898) is resurrected from synonymy with Melanochaeta Bezzi,1906. Currently an application is with the ICZN (case 3576) to conserve Oscinella Becker, 1909 by reversed precedence of both Melanochaeta Bezzi, 1906 and Pachychaetina Hendel, 1907. Wing reduction in Chloropidae is also discussed.